Safety and feasibility of low‐dose ticagrelor in patients with ST‐segment elevation myocardial infarction. Issue 1 (15th December 2020) - Wang, Yanbo; Jiang, Yunfa; Zhi, Wei; Fu, Yang; Wang, Qing; Zhou, Jianli; Zheng, Shaochen; Hao, Guozhen
Abstract: Background: Previous studies have confirmed the safety and feasibility of half‐dose ticagrelor in Chinese patients with acute coronary syndrome, but currently there is no plan for the use of ticagrelor for Chinese ST‐segment elevation myocardial infarction (STEMI) patients. Hypothesis: It is safe and feasible of low‐dose ticagrelor in patients with STEMI. Methods: The STEMI patients who were undergoing emergency intervention and taking ticagrelor were enrolled. Patients whose level of platelet aggregation rate (PAR) less than 30% after 7‐day treatment with standard‐dose ticagrelor were randomly divided into low‐dose group (LD group, 45 mg twice daily) and standard‐dose group (SD group, 90 mg twice daily). The changes of levels of platelet parameters were compared between the two groups. The incidence of major adverse cardiac events (MACE), bleeding events were compared between the two groups within 6 months of follow‐up. Results: The levels of PAR in the SD group decreased compared with baseline, and was lower than those of LD group at the same time point. The levels of platelet distribution width in both groups decreased from the baseline values (all p < .05) at 1, 3, and 6 months after grouping treatment, but there was no significant difference between the two groups. The incidence of MACE was similar between the two groups of patients. There were decreasing trends in the incidences of minimal bleeding event, minor bleeding event, dyspnea, and gout in the LD group. Conclusion: It is safe and feasible of low‐dose ticagrelor for patients with STEMI based on the monitoring of PAR.